High Circulating Sonic Hedgehog Protein Is Associated With Poor Outcome in EGFR-Mutated Advanced NSCLC Treated With Tyrosine Kinase Inhibitors - Takam Kamga, Paul; Swalduz, Aurélie; Costantini, Adrien; Julié, Catherine; Emile, Jean-François; Pérol, Maurice; Avrillon, Virginie; Ortiz-Cuaran, Sandra; de Saintigny, Pierre; Giroux-Leprieur, Etienne (Frontiers in Oncology, 2021)
Introduction: Growing preclinical evidence has suggested that Sonic hedgehog (Shh) pathway is involved in resistance to Tyrosine Kinase Inhibitors (TKI) therapy for EGFR-mutated (EGFRm) non-small cell lung cancer (NSCLC). However, little is known concerning the prognostic value of this pathway in this context. Materials and Methods: We investigated the relationship between plasma levels of Shh and EGFRm NSCLC patients’ outcome with EGFR TKIs. We included 74 consecutive patients from two institutions with EGFRm advanced NSCLC treated by EGFR TKI as first-line therapy. Plasma samples were collected longitudinally for each patient and were analyzed for the expression of Shh using an ELISA assay. Immunohistochemistry was used to analyze Gli1 expression in tumor biopsies. Results: Shh protein was detectable in all samples at diagnosis (mean = 1041.2 ± 252.5 pg/ml). Nuclear expression of Gli1 was observed in 57.1 % (8/14) of patients’ biopsies. Shh was significantly (P<0.05) enriched in youth (age < 68), male, nonsmokers, patients with a PS > 1, patients presenting more than 2 metastatic sites, and L858R mutation. Higher levels of Shh correlated with poor objective response to TKI, shorter progression-free survival (PFS) and T790M-independent mechanism of resistance. Conclusion: These data support that higher levels of plasma Shh at diagnosis is associated with poor outcome with EGFR-TKI, suggesting that Shh levels could stand as a prognostic biomarker for the management of EGFR-mutated NSCLC patients treated with EGFR-TKI.